Zero hour - Bentley, Don; Clancy, Tom, 1947-2013 (Clancy, Tom, 1947-2013. Jack Ryan Jr. novel, 2022)
When the leader of North Korea is catastrophically injured, his incapacitation inadvertently triggers a "dead-man's switch," activating an army of sleeper agents in South Korea and precipitating a struggle for succession. Jack Ryan, Jr. is in Seoul to interview a potential addition to the Campus. When a wave of violence perpetrated by North Korean operatives grips South Korea's capital, Jack races to discover the meaning behind an ominous one-word text sent by a mysterious North Korean contact: Run. -- adapted from jacket